Volatility spillovers between the European and South African foreign exchange markets - Olivier Niyitegeka; Devi D. Tewari (Cogent Economics & Finance, 2020)
This article investigates the exchange rate volatility spillover and dynamic conditional correlation between the euro and the South African rand following the Eurozone sovereign debt crisis. It employs two multivariate generalized autoregressive conditional heteroskedasticity (MGARCH) models, namely bivariate BEKK-GARCH (1,1) a nd DCC-GARCH(1,1). Based on two datasets, for the crisis and post-crisis periods, the study identifies significant uni-directional volatility spillovers from the euro to the rand during crisis and post-crisis periods. Further, increased volatility spillovers and time-varying correlations between currencies were evident during the Eurozone crisis. This suggests pure form of financial contagion between the two foreign exchange markets. As such, investors and policy makers in the stock and/or foreign exchange markets in South Africa should monitor euro volatility due to its contagious impacts on the rand and decoupling strategies should be formulated to insulate the rand from contagion. The contributions of the study are twofold. First, it informs the investors in the foreign exchange market on the extent to which shocks in the euro affect the rand. Second, it adds to the literature on pure form of contagion by testing whether there exists an asymmetric correlation between the rand and euro over tranquil periods as opposed to financial upheaval ones.
Keywords: C32; F31; G15; 330; BEKK-GARCH; DCC-GARCH; volatility spillover; contagion test